Cytochrome P450 93G1 Is a Flavone Synthase II That Channels Flavanones to the Biosynthesis of Tricin O-Linked Conjugates in Rice . Issue 3 (19th May 2014) - Lam, Pui Ying; Zhu, Fu-Yuan; Chan, Wai Lung; Liu, Hongjia; Lo, Clive
Abstract : The rice cytochrome P450 enzyme CYP93G1 is a phylogenetically unique flavone synthase II that converts flavanones directly to flavones, a key branch point reaction leading to the production of tricin O-linked glycosides and flavanolignans . Abstract: Flavones are a major class of flavonoids with a wide range of physiological functions in plants. They are constitutively accumulated as C -glycosides and O -linked conjugates in vegetative tissues of grasses. It has long been presumed that the two structural modifications of flavones occur through independent metabolic routes. Previously, we reported that cytochrome P450 93G2 (CYP93G2) functions as a flavanone 2-hydroxylase (F2H) that provides 2-hydroxyflavanones for C -glycosylation in rice ( Oryza sativa ). Flavone C -glycosides are subsequently formed by dehydratase activity on 2-hydroxyflavanone C -glycosides. On the other hand, O -linked modifications were proposed to proceed after the flavone nucleus is generated. In this study, we demonstrate that CYP93G1, the closest homolog of CYP93G2 in rice, is a bona fide flavone synthase II (FNSII) that catalyzes the direct conversion of flavanones to flavones. In recombinant enzyme assays, CYP93G1 desaturated naringenin and eriodictyol to apigenin and luteolin, respectively. Consistently, transgenic expression of CYP93G1 in Arabidopsis ( Arabidopsis thaliana ) resulted in the accumulation of different flavone O -glycosides, which are not naturally present in cruciferous plants. Metabolite analysis of a rice CYP93G1 insertion mutant further demonstrated the preferential depletion of tricin O -linked flavanolignans and glycosides. By contrast, redirection of metabolic flow to the biosynthesis of flavone C -glycosides was observed. Our findings established that CYP93G1 is a key branch point enzyme channeling flavanones to the biosynthesis of tricin O -linked conjugates in rice. Functional diversification of F2H and FNSII in the cytochrome P450 CYP93G subfamily may represent a lineage-specific event leading to the prevalent cooccurrence of flavone C - and O -linked derivatives in grasses today.